Tantrābhidhānam : varṇābhidhāna-mātrkānighaṇṭu-varṇanighaṇṭu-varṇabījābhidhānaikākṣarakoṣa-mantrārthābhidhāna-mudrānighaṇṭu-varṇabījakoṣarūpam - Śāstrī, Pañcānana (Nababhārata Pābaliśārsa, 1978)
Tantric dictionary.